Pembuatan Kerajinan Sumpit (Tandok) untuk Meningkatkan Ekonomi Pelaku UMKM Desa Pentai Cermin Kiri Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Abdurrozzaq Hasibuan; Kimberly Febrina Kodrat; Siti Rahmah Subuea; Fitri Wulan Dari; Rizki Ananda (Cattleya Darmaya Fortuna, 2024)
The making of tandok handicrafts in Pantai Cermin Kiri Village, Pantai Cermin Sub-district, Serdang Badagai Regency has a role in improving the community's economy. But on the other hand, there are problems in developing skills and diligence in making woven crafts. Many people in Pematang Panjang Village work as farmers or agricultural laborers. Similarly, the youth of Pantai Cermin Kiri Village have chosen to work outside the city. This research uses a qualitative method that emphasizes the descriptive qualitative type. The data collection technique used was focus group discussion. The results that have been achieved in the implementation of training on the development of woven handicrafts are (1) increasing the skills of craftsmen in making tandok products; (2) increasing the competitiveness of tandok handicraft production; (3) increasing the economy of the Pantai Cermin Kiri Village community, Pantai Cermin Sub-district, Serdang Badagai Regency.